SIMBIOSES: Modelling Industrial Metabolism in a Multi-Regional Economic System - Marco A. Janssen; Jeroen C.J.M. van den Bergh (Tinbergen Institute, 1999)
A model framework, SIMBIOSES, is presented which describes economic activities and relatedmaterial, substance and energy flows in a multi-region and multi-sector economic system. Theconceptual design of the framework is discussed in relation to current issues on dematerializationand decoupling.Three types of models to implement SIMBIOSES are discussed: a static equilibrium model,a dynamic optimisation model, and a system dynamics model. The static model determines thestatic equilibrium of extraction, production, recycling, and energy recovery from waste. Thedynamic model determines the long-term investment decision that optimises total discounted utilityof consumption. The dynamic model incorporates technological change, allocation of resources,and damage costs due to accumulation of substances in the environment. The system dynamicmodel generates endogenous economic growth and technology development and includes boundedrationality of economic agents.
Keywords: 330; dematerialization; mass balance; integrated models; Environmental Kuznets curve; equilibrium analysis; dynamic optimisation; system dynamics; Input-Output-Analyse; Stoffstrommanagement; Gleichgewichtstheorie; Theorie